2019
DOI: 10.3390/agronomy9080413
|View full text |Cite
|
Sign up to set email alerts
|

Development and Application of Seed Coating Agent for the Control of Major Soil-Borne Diseases Infecting Wheat

Abstract: In order to reduce the usage amount of pesticide fertilizers and protect the natural environment, seed coating agents are receiving increased wide concern. In this study, the active constituent (pesticide) and inactive components (surfactants and film former) of the seed coating agents were screened and optimized by the wet sand processing superfine grinding method. The fungal inhibition test of pesticides showed that thifluzamide, fludioxonil, pyraclostrobin, and difenoconazole have an obvious fungal inhibito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 18 publications
(21 reference statements)
1
9
0
Order By: Relevance
“…With these considerations in mind and in an effort to reduce the use of petroleum‐based polymers, biopolymers have gained increasing popularity as seed coating materials due to their biodegradability, good film‐forming properties, and being nontoxic and ecofriendly. Among others, cellulose and its derivatives, [ 74 ] chitosan, [ 75,76 ] starch, [ 77 ] alginate, [ 78 ] gum arabic, [ 79 ] gelatin, [ 80 ] and soy protein [ 81 ] are some of the biopolymers that have been widely used in seed coatings for targeted delivery of active ingredients. More recently, the use of silk fibroin—a structural protein extracted from Bombyx mori cocoons in the design of functional seed coatings has opened up new possibilities for sustainable agriculture on marginal lands.…”
Section: Sustainable Agriculturementioning
confidence: 99%
“…With these considerations in mind and in an effort to reduce the use of petroleum‐based polymers, biopolymers have gained increasing popularity as seed coating materials due to their biodegradability, good film‐forming properties, and being nontoxic and ecofriendly. Among others, cellulose and its derivatives, [ 74 ] chitosan, [ 75,76 ] starch, [ 77 ] alginate, [ 78 ] gum arabic, [ 79 ] gelatin, [ 80 ] and soy protein [ 81 ] are some of the biopolymers that have been widely used in seed coatings for targeted delivery of active ingredients. More recently, the use of silk fibroin—a structural protein extracted from Bombyx mori cocoons in the design of functional seed coatings has opened up new possibilities for sustainable agriculture on marginal lands.…”
Section: Sustainable Agriculturementioning
confidence: 99%
“…Both binders and fillers need to be compatible with the AIs. It has been recently reported that coating the seeds helps to enhance the plant stress tolerance during seed germination and seedling growth [ 27 ]. In an attempt to reduce the fossil fuel–based polymers and owing to the biodegradable nature, ease of availability, and generally low cost of the precursors, biodegradable polymers have been used in seed coating over the last two decades.…”
Section: Biodegradable Seed Coatingsmentioning
confidence: 99%
“…Ren et al. [ 27 ] have developed a polyacrylamide and carboxymethylcellulose–based seed coat for wheat seeds using various fungicides and additives to investigate the effect of seed coating on germination and growth of wheat. To improve the seed coating efficiency, Berninger et al.…”
Section: Biodegradable Seed Coatingsmentioning
confidence: 99%
“…In addition, the mycelium of wheat sheath blight and root rot can also live through the winter in the soil and inside and outside the seeds, respectively. Wheat sharp eyespot caused by Rhizoctonia cerealis van der Hoeven and root rot by Bipolaris sorokiniana are important typical soil-borne diseases threatening wheat production worldwide [6]. Wheat sharp eyespot can infect the stems and sheaths of wheat plants, leading to a block in nutrient transportation.…”
Section: Introductionmentioning
confidence: 99%